2023
DOI: 10.1021/acs.orglett.2c04223
|View full text |Cite
|
Sign up to set email alerts
|

Access to Functionalized Thiazolothiadiazoles via the Chemoselective Cascade Heteroannulation of Thioamides with Hypervalent Iodine Reagents

Abstract: We describe herein a chemo- and regioselective cascade annulation between β-ketothioamides and diazo-substituted hypervalent iodine reagents under transition-metal-free and base-free conditions at room temperature. Thus, a divergent construction of fused-heterocyclic scaffold thiazolothiadiazoles has been achieved with the advantages of operational simplicity, scalability, broad substrate compatibility, and mild reaction conditions. This one-pot strategy not only avoids potential toxicity but also broadens the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Singh et al [84] . devised a one‐pot, transition metal‐free, base‐free synthetic method for the efficient regioselective and stereoselective synthesis of biologically important scaffolds thiazolothiadiazoles 102 in the presence of DCM at room temperature.…”
Section: Synthesis Of Thiazolesmentioning
confidence: 99%
See 1 more Smart Citation
“…Singh et al [84] . devised a one‐pot, transition metal‐free, base‐free synthetic method for the efficient regioselective and stereoselective synthesis of biologically important scaffolds thiazolothiadiazoles 102 in the presence of DCM at room temperature.…”
Section: Synthesis Of Thiazolesmentioning
confidence: 99%
“…Singh et al [84] devised a one-pot, transition metal-free, basefree synthetic method for the efficient regioselective and stereoselective synthesis of biologically important scaffolds thiazolothiadiazoles 102 in the presence of DCM at room temperature. Functionalized beta-keto thioamides 100 in reaction with hypervalent iodine substituents 101 were observed to procure the desired fused N-heterocyclic compounds in moderate to excellent yield.…”
Section: Synthesis Of Thiazoles Through the Cà C Cà N Coupling And Cà...mentioning
confidence: 99%
“…[71] In 2023, Singh and co-workers synthesized functionalized thiazolothiadiazoles 51 via the cascade heteroannulation of thioamides 50 with diazomethyl-substituted iodine(III) compounds 3 (Scheme 17). [72] This synthesis method was achieved by constructing the C(sp 2 )À S bond through the nucleophilic pathway. The authors have examined a broad range of β-ketothioamides 50 and compounds 3 showing adaptability to reaction conditions, and found that these substrates exhibited good tolerance and generated thiazolothiadiazoles 51 in 60-81 % yields.…”
Section: C(sp 2 )à S Bond-forming Reactionsmentioning
confidence: 99%
“…In 2023, Singh and co‐workers synthesized functionalized thiazolothiadiazoles 51 via the cascade heteroannulation of thioamides 50 with diazomethyl‐substituted iodine(III) compounds 3 (Scheme 17). [72] This synthesis method was achieved by constructing the C(sp 2 )−S bond through the nucleophilic pathway. For example, compound 3 was nucleophilic attacked by thioamide 50 to construct C(sp 2 )−S bond and generate intermediate A , which underwent an intramolecular cyclization and eliminated aniline to provide thiadiazolium salt B .…”
Section: Nucleophilic Reactionsmentioning
confidence: 99%
“…Environmentally benign hypervalent iodine reagents are considered as effective alternatives to heavy metal oxidants and expensive organometallic catalysts in many metal-free organic transformations . Several organic iodine­(III) reagents are well-known for their functional group transferring ability . Among them, the imino-λ 3 -iodane-based reagents are sulfonyl amino group surrogates and also act as aminating reagents.…”
mentioning
confidence: 99%